The efficacy of Merit-based Recruitment in Amolatar district in Northern Uganda - Ocwer, Bruno; Okuna, Victor; Mwesigwa, David (Human Resource and Leadership Journal, 2024)
Purpose: This study aimed to assess the success of merit-based recruitment in Amolatar District Local Government Administration, Uganda. Methodology: A case-study research design was adopted backed by quantitative and qualitative analysis that involved a careful and in-depth investigation of a particular unit or events under study for the purposes of generalization. It was conducted in Amolatar District. We chose this area because merit-based recruitment had failed as a result of weak decision-making processes by the district service communion and the influence-peddling by political leaders in the district. We took a sample of 60 respondents and interviewed 52 respondents living within the District Headquarters and in Amolatar Town Council. Findings: The results revealed that the success of merit-based recruitment in Local Government Administration is very essential in terms of stakeholder responsibility, enhancing citizen confidence in the local government institution, and enabling the district service commission to recruit the best human resources for the provision of quality service. Contribution to Theory, Policy and Practice: This study is central as it strengthens the merit-based recruitment model over and above other models of recruitment as well as enabling local governments to prioritize meritocracy over political patronage in every staff recruitment cycle.